ANALISIS EFEKTIVITAS METODE TEBAK GAMBAR DALAM MENGEMBANGKAN BAHASA RESEPTIF SISWA - Khofifah, Eva Nur; Fatimah, Nurul; Tartila, Zakiyana; Ilyas, Muhammad (PGMI Department of Institut Agama Islam Ibrahimy Genteng Banyuwangi, Indonesia, 2025)
This study aims to examine the effectiveness of using the